A proof-of-concept study on endoscopic ultrasound-guided biopsy of detrusor muscle in porcine bladders - Teoh, Jeremy Yuen-Chun; Cho, Chak-Lam; Chan, Ronald Cheong-Kin; Liu, Kang; Zhao, Hongda; Giannarini, Gianluca; Enikeev, Dmitry; Ng, Chi-Fai; Teoh, Anthony Yuen-Bun (Frontiers in Oncology, 2023)
Conventionally, we rely on transurethral resection of bladder tumour (TURBT) for local staging of muscle-invasive bladder cancer (MIBC). However, the procedure is limited by its staging inaccuracy which may delay the definitive treatment of MIBC. We conducted a proof-of-concept study on endoscopic ultrasound (EUS)-guided biopsy of detrusor muscle in porcine bladders. Five porcine bladders were used in this experiment. Upon EUS, four layers of tissue including the mucosa (hypoechoic), submucosa (hyperechoic), detrusor muscle (hypoechoic) and serosa (hyperechoic) could be identified clearly. A total of 37 EUS-guided biopsies were taken from 15 sites (three sites per bladder), and the mean number of biopsies taken from each site was 2.47±0.64. Among the 37 biopsies, 30 of them (81.1%) obtained detrusor muscle in the biopsy specimen. For the per biopsy site analysis, detrusor muscle was obtained in 73.3% if only one biopsy was taken, and 100% if two or more biopsies were taken from the same biopsy site. Overall, detrusor muscle was successfully obtained from all 15 biopsy sites (100%). No bladder perforation was observed throughout all biopsy processes. EUS-guided biopsy of the detrusor muscle could be performed during the initial cystoscopy session, thus expediting the histological diagnosis and subsequent treatment of MIBC.